Analysis of the Quality of Public Services for the Village of Torosiaje Village, Popayato District, Pohuwato Regency, Gorontalo Province - Setri Pasandre; Siske Anani; Djamila Podungge (Journal of Economic, Business, and Administration (JEBA), 2021)
Public Service Activities to the community carried out by public service providers see public service as the most important aspect in the village as a government, it is proper for village officials to pay attention to the quality of public services in the village. The village government regulates and also takes care of the interests of the community in the village itself so that the village apparatus as government must provide services that are in accordance with the expectations of the community to run well. This study aims to determine the quality of public services in Torosiaje Village. This type of research is a descriptive study with a qualitative approach. The types of data used in this study are primary data and secondary data with data sourced from observations, interviews and documentation. The number of informants in this study was 5 (five) people who were the people of Torosiaje Village and the Head of Service. The results of the study show that the quality of public services in people's perceptions of the quality of public services is quite good, seen from the indicators of the quality of public services, although there are usually obstacles in service, but it does not reduce the village apparatus in public services. although there is usually a delay in other services because there are other needs that must be done but it will not reduce the public services of the Torosiaje village apparatus in providing public services for the community